INTERAKSI SOSIAL SUKU SUNDA DENGAN SUKU JAWA (Kajian Akulturasi dan Akomodasi Di Desa Buko Poso, Kecamatan Way Serdang, Kabupaten Mesuji Tahun 2016) - Rendra Havid Pranata; Kuswono Kuswono (Swarnadwipa, 2021)
Social interaction is very important in everyday life. Social interaction is necessary to create a social relationship between individuals between individuals or between groups with one another. In a community group has a relationship between tribes manifested as relationships between individuals or between groups of tribal people with each other who live next door and get along with each other. In this study aims to describe the social interaction and the results of the interaction itself which focuses on the study of acculturation and accommodation of the Sundanese tribe with Javanese tribe in the village of Buko Poso sub district of Serdang. The problem in this research is social interaction of Sundanese Tribe with Java Tribe in Buko Poso Village, Way Serdang Subdistrict, Mesuji Regency. Looking at social reality as a whole, complex, dynamic, and symptomatic relationship is interactive. In this research the research method that researchers use in this research is qualitative research method. The result of this research is the social interaction of Sundanese with Javanese Tribe is a positive interaction. Both tribes interact daily. Sundanese and Javanese live side by side and are very respectful and highly uphold tolerance.